Communion to community building: a study of the opportunities of community capitals after religious facilities are adaptively reused - Baniqued, Julie Nicole (Kansas State University, 2022)
Religious groups and their places of worship have played important roles in community development throughout history, specifically regarding social, cultural, human, and built capital in their communities. Today, more religious facilities are becoming vacant and presenting opportunities for adaptive reuse than ever before. Factors like white flight (Woldoff, 2011), smaller congregation sizes (Simons, et. al., 2017), fewer religious leaders and church consolidations after COVID-19 (Cullotta, 2021; Lovett, 2022), and migration of religious groups to the suburbs (Conzen, 2005) has resulted in the increase of vacant religious facilities in cities. Consequently, many places across the U.S. are tasked with figuring out how to address these large vacant spaces that are harder to fill and to transform when many residents still consider them sacred. In Chicago, religious facilities are adaptively reused into a variety of new uses, but more recently are skewing towards residential. This has sparked the debate among community members about highest and best use for former religious facilities that continues today (Gunderson, 2019). Some residents and professionals argue that the adaptively reused religious facilities should have community uses, such as community arts centers, to preserve the important roles that institutional uses played in communities in the past. Others argue that communities benefit greatly also when the religious facilities are adaptively reused into a non-community use, such as residential, so the new use should be whatever is economically feasible and has a demand. For a planner, it is important to maximize health, safety, and economic wellbeing of everyone living in a community as it grows and changes, and that includes encouraging the uses that build stronger communities with the greatest opportunities for community capitals. In this report, multiple cases are studied to discuss the similarities and differences in opportunities for social, cultural, human, and built capital after religious facilities were adaptively reused in Chicago. In order to provide a more holistic perspective to this research, background on the social and economic changes over the last thirty years in Chicago was included. Though the socio-economic background does not pinpoint the exact causes why religious facilities became vacant and the specific new uses were chosen for those buildings, it does enrich the understanding of what factors may influence these projects and who might be impacted by them. Overall, this investigation of the opportunities for community capitals through the focus of adaptively reused religious facilities shows how new community and non-community uses have impacted their surrounding community areas.
Keywords: Adaptive reuse; Religious facilities; Community capitals